The Contribution of Moisture Sources of Precipitation to Water Resources Recharge in Semi-Arid Regions - Hossein Mohammadzadeh; Rogert Sorí; Mojtaba Heydarizad (Atmosphere)
This study investigates the isotopic composition of precipitation in Iran and its moisture sources, offering insights crucial for addressing water recharge and management in semi-arid regions. This study analyzes 150 precipitation events collected from 11 stations across Iran over multiple years. The HYSPLIT model was used to trace air mass trajectories contributing to these events. The isotopic composition of precipitation from each moisture source was examined to identify their distinct characteristics. Furthermore, the contribution of each air mass to groundwater and surface water recharge was quantified using the Simmr mixing model in R programming language, combining stable isotope data from precipitation and surface/groundwater samples. Precipitation in northern Iran is associated with low d-excess values, indicating moisture from high-latitude sources, particularly the Caspian Sea, while higher d-excess values in the west and south point to moisture mainly from the Persian Gulf and the Mediterranean Sea. Air mass trajectory analysis via the HYSPLIT model identified the dominant pathways of Continental Tropical (CT), Continental Polar (CP), and Mediterranean (MedT) air masses across Iran. Quantitative analysis using the Simmr mixing model revealed that the CT air mass contributes up to 33.6% to groundwater recharge in southern Iran’s karstic regions, while the CP air mass dominates in the north, with up to 46.8% contribution. The MedT air mass, although significant in the west, decreases in influence towards the east. Isotope data from groundwater and surface water sites showed more depleted values than local precipitation, likely due to larger catchment areas. These findings contribute to water management strategies by identifying the variations in moisture sources that influence groundwater and surface water recharge in Iran. Understanding these variations enables the development of targeted strategies for managing water resources in semi-arid regions facing increasing water scarcity. The methodologies applied in this study can be adapted to other regions, providing a valuable framework for sustainable water management in areas where identifying moisture sources is critical.